The effect of graded fibrous structure of bamboo (Phyllostachys edulis) on its water vapor sorption isotherms - Chen, Qi; Wang, Ge; Ma, Xin-Xin; Chen, Mei-Ling; Fang, Chang-Hua; Fei, Ben-Hua (Industrial crops and products, 2020)
[Display omitted] •Equilibrium moisture content of bamboo decreased from the inner to the outer at the radial position.•Fiber cell absorbed water mainly by forming hydrogen bonds between water and hydroxyl groups in the cell wall.•Parenchyma cell absorbed water via bonding to hydroxyl groups and forming water clusters. Hygroscopic behavior is an inherent characteristic of bamboo that strongly affects its mechanical properties, durability, and dimensional stability. In order to understand the effects of the unique graded fibrous structure of bamboo on its water vapor sorption behavior, this study used bamboo specimens (Phyllostachys edulis) collected from the inner to the outer part of culm wall to test the equilibrium moisture content (EMC) and hysteresis. A dynamic vapor sorption apparatus was used to measure the EMC of bamboo slices at relative humidity (RH) ranging from 0 to 95 % at a constant temperature of 25 °C. The results were analyzed by calculating the EMC of fiber and parenchyma cells and using the Guggenheim-Anderson-de Boer (GAB), Hailwood -Horrobin (H-H), and Henderson models. It was shown that the EMC of bamboo at varied radial positions of culm wall were different, especially at high RH. The EMCs of the inner and outer part were 26.7 % and 18.0 % at 95 % RH, respectively. It was also noted that fiber cell absorbed water mainly by forming hydrogen bonds between water and hydroxyl groups in the cell wall during the whole RH range, while parenchyma cell absorbed water via bonding to hydroxyl groups at low RH (below 60 %) and through forming water clusters at high RH (over 60 %). The hysteresis value increased from the inner to the outer part. Three models fitted the experimental data satisfactorily and can be used to calculate the monolayer moisture content. These models also confirm that the outer part of bamboo culm wall provided more sorption sites for water than the inner part, while more water clusters were formed in the inner part.